2019
DOI: 10.1101/631341
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Bidirectional Network for Appetite Control in Larval Zebrafish

Abstract: 14Medial and lateral hypothalamic loci are known to suppress and enhance appetite, respectively, 15 but the dynamics and functional significance of their interaction have yet to be explored. Here 16we report that, in larval zebrafish, primarily serotonergic neurons of the ventromedial caudal 17 hypothalamus (cH) become increasingly active during food deprivation, whereas activity in the 18 lateral hypothalamus (LH) is reduced. Exposure to food sensory and consummatory cues 19 reverses the activity patterns of … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 63 publications
(89 reference statements)
1
13
0
Order By: Relevance
“…It has been reported that zebrafish exposed to Trans-2phenylcyclopropylamine (PCPA), a non-selective MAO inhibitor, present increased neuronal death (Jie et al, 2009). Contributions of these hypothalamic systems to behaviors in larval zebrafish have been described, including regulation of feeding (Wee et al, 2019). Additionally, zebrafish swim bladder has been reported to receive serotonergic input (Finney et al, 2006) and mao inhibition is known to affect swim bladder control in zebrafish (Sallinen et al, 2009b), which could have compromised the ability of the larvae to move and seek for food.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that zebrafish exposed to Trans-2phenylcyclopropylamine (PCPA), a non-selective MAO inhibitor, present increased neuronal death (Jie et al, 2009). Contributions of these hypothalamic systems to behaviors in larval zebrafish have been described, including regulation of feeding (Wee et al, 2019). Additionally, zebrafish swim bladder has been reported to receive serotonergic input (Finney et al, 2006) and mao inhibition is known to affect swim bladder control in zebrafish (Sallinen et al, 2009b), which could have compromised the ability of the larvae to move and seek for food.…”
Section: Discussionmentioning
confidence: 99%
“…Neuromodulation could also contribute to the gain control of prey capture behavior observed in this study. The dopaminergic system encodes stimulus valence and regulates motivation Matsumoto and Hikosaka, 2009 ; the noradrenergic locus coeruleus is thought to modulate arousal Carter et al, 2010 ; different parts of the hypothalamus are thought to control a variety of motivational functions like arousal and feeding ( Mahler et al, 2014 ; Wee et al, 2019 ). The central amygdala has recently been shown to control predatory hunting in mice, by increasing capture initiation via the periaqueductal gray ( Han et al, 2017 ), which is homologous to the griseum centrale of zebrafish, and receives input from the habenula ( Olson et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…One group of eurydendroid cells projected to the dorsal zone of the periventricular hypothalamus (Figure 4D, cluster 4), an area involved in satiety response (Wee et al, 2019). Strikingly, this brain region was also strongly stained for cfos expression during prey capture behavior (Suppl.…”
Section: Discovery Of Behaviorally Relevant Circuits Using Cfos Fishmentioning
confidence: 98%